Defective insulin-stimulated GLUT4 translocation in brown adipocytes induces systemic glucose homeostasis dysregulation independent of thermogenesis in female mice - Belén Picatoste; Lucie Yammine; Rosemary A. Leahey; David Soares; Emma F. Johnson; Paul Cohen; Timothy E. McGraw (Elsevier, 2021)
Objective: Recent studies indicate that brown adipose tissue, in addition to its role in thermogenesis, has a role in the regulation of whole-body metabolism. Here we characterize the metabolic effects of deleting Rab10, a protein key for insulin stimulation of glucose uptake into white adipocytes, solely from brown adipocytes. Methods: We used a murine brown adipocyte cell line and stromal vascular fraction-derived in vitro differentiated brown adipocytes to study the role of Rab10 in insulin-stimulated GLUT4 translocation to the plasma membrane and insulin-stimulated glucose uptake. We generated a brown adipocyte-specific Rab10 knockout for in vivo studies of metabolism and thermoregulation. Results: We demonstrate that deletion of Rab10 from brown adipocytes results in a two-fold reduction of insulin-stimulated glucose transport by reducing translocation of the GLUT4 glucose transporter to the plasma membrane, an effect linked to whole-body glucose intolerance and insulin resistance in female mice. This effect on metabolism is independent of the thermogenic function of brown adipocytes, thereby revealing a metabolism-specific role for brown adipocytes in female mice. The reduced glucose uptake induced by Rab10 deletion disrupts ChREBP regulation of de novo lipogenesis (DNL) genes, providing a potential link between DNL in brown adipocytes and whole-body metabolic regulation in female mice. However, deletion of Rab10 from male mice does not induce systemic insulin resistance, although ChREBP regulation is disrupted. Conclusions: Our studies of Rab10 reveal the role of insulin-regulated glucose transport into brown adipocytes in whole-body metabolic homeostasis of female mice. Importantly, the contribution of brown adipocytes to whole-body metabolic regulation is independent of its role in thermogenesis. It is unclear whether the whole-body metabolic sexual dimorphism is because female mice are permissive to the effects of Rab10 deletion from brown adipocytes or because male mice are resistant to the effect.